Antimicrobial Activity of Natural Solid Soap with a Combination of Liquid Cheese Waste, Turmeric (Curcuma longa), and Dragon Fruit (Hylocereus polyrhizus) Peel - Estikomah, Solikah Ana; Suranto, Suranto; Susilowati, Ari; Masykuri, Mohammad (Molekul, 2023)
Yoghurt whey is a product from fermented cheese liquid waste. Yoghurt cheese liquid waste has been known to contain lactoferrin. Lactoferrin functions as an antimicrobial. yoghurt made from whey has not been widely utilized as a solid soap ingredient. This research focuses on producing solid natural soap made of yoghurt whey with added natural dye turmeric and dragon fruit peel, soap quality testing, and analysis of the soap's antibacterial activity toward Staphylococcus aureus. The solid soap was processed through the saponification reaction between palm oil, coconut oil, zaitun oil, and canola oil with sodium hydroxide. Variations of yogurt whey used in this study yoghurt 25%,75%,100% whey) was added natural dye (turmeric and dragon fruit peel). The quality test was done by determining free alkali, water content, pH, and foam height. Antibacterial activity test using the well diffusion method. The result shows that the quality test yoghurt soap meets with INS (Indonesia National Standard) 2016, for all the criteria. Performs inhibition against bacteria Staphylococcus aureus. Yoghurt whey is potently used as an antibacterial agent in the manufacture of natural solid soap.